Disseminated epithelial cancers-An autopsy analysis - Pradeep Vaideeswar; Sachin Patil; Jayashri Chaudhari (Wolters Kluwer Medknow Publications, 2022)
Background: Cancer is one of the leading causes of death due to noncommunicable diseases worldwide. Despite increasing public awareness and availability of sophisticated imaging techniques, some cancers evade clinical diagnosis and/or are incidentally encountered at autopsies, often with dissemination. Aims: The present study evaluated the disseminated epithelial cancers at autopsy. Materials and Methods: This is a retrospective observational 5-year autopsy analysis of disseminated epithelial cancers performed at a tertiary-care hospital. The cases were categorized as (1) clinically diagnosed malignancy, known primary; (2) clinically diagnosed malignancy, unknown primary; and (3) clinically undiagnosed malignancy. Statistical Analysis: Nil. Results: Dissemination was identified in 66 (57.9%) of the 114 patients with epithelial malignancies. There were 29 patients (43.9%) in category 1, 26 patients (39.4%) in category 2, and 11 patients (16.7%) in category 3, majority of whom were women (38 patients, 57.6%). When all categories were considered together, lung and colorectal carcinomas were the commonest cancers seen in 13 (19.7%) and 8 (12.1%) patients, respectively, in both men and women. Majority of the patients (43 cases, 65.2%) had symptoms produced by metastases, which were the sole manifestations in 13 patients (19.7%). Lungs and liver were the common metastatic sites. Conclusions: Cancerous dissemination continues to be a major cause of morbidity and mortality even after considerable improvements in the surgical or nonsurgical treatment modalities. An autopsy study can provide important clinical insights in retrospect.